Accounting of the Enterprise's Financial Reserves at the Integration of Energy-Saving Principles and Transition to the Concept of Energy-Saving Production - Amanova, Gulnara D.; Akimova, Bibigul Zh.; Kazhmukhametova, Asem A.; Moldashbayeva, Luiza P.; Urazbayeva, Zinegul O.; Danayeva, Ryskul S. (International Journal of Energy Economics and Policy, 2020)
The main task of modern production is to form the program of development and determination of the ways for technological improvement. The relevance of the work is in the fact that the technological concept for energy-saving development is almost always connected with the focus on it on the part of the company's management. In particular, with the availability of energy costs for the enterprise, the issue of energy saving is not formed as relevant. In conditions when all the enterprises are increasingly entering the global market and obtaining resources at prices of the world's manufacturers, there is a necessity of updating of the energy conservation system and the revitalization of the study's problematics. The novelty of the study is determined by the fact that it has investigated the means of accounting for the use of energy-saving measures in order to form a sustainable operation of the enterprise. The paper shows the aspects of the greening of an industrial enterprise in the implementation of the energy-saving program. The organizational, structural and technological features of accounting activities have been revealed in the economic reporting of the enterprise. The practical application of the study is possible provided that the company fully contributes to the goals of entering the international market and assesses their performance according to the international reporting standards. Keywords: Energy Enterprise, Reporting, Accounting, International Market, Greening JEL Classifications: K32, L3, L32 DOI: https://doi.org/10.32479/ijeep.8669